Studying the Relationship between CO2 Emissions and Renewable Energy: A Threshold ARDL and NARDL Panel Econometric Analysis - Sallam, Mohamed A. M.; Sadraoui, Tarek (International Journal of Energy Economics and Policy, 2025)
This study examines the dynamic relationship between CO2 emissions and renewable energy consumption across a panel of countries from 2000 to 2025. Unlike the conventional approach, we employ both Threshold Autoregressive Distributed Lag (TARDL) and Non-linear ARDL (NARDL) models to account for potential asymmetric and threshold effects in both the short- and long-run relations. Our results reveal substantial nonlinearities, whereby the uptake of renewable energy decreases CO2 emissions more efficiently beyond specific threshold points. Asymmetric emission responses to positive and negative changes in renewable energy are also identified, underscoring the need for policy initiatives tailored to the speed of the energy transition. The findings have important implications for policymakers seeking to attain goals of sustainable energy and combat climate change.